Exergetic calculation of the efficiency of heat pump installations for a private building - О. Стенін; В. Пасько; М. Солдатова; І. Дроздович (Adaptivni Sistemi Avtomatičnogo Upravlinnâ, 2025)
Despite the fact that important results have been obtained in a number of works that facilitate the calculation and design of heat supply systems based on ground heat pump installations taking into account the thermophysical processes occurring in the soil, at the same time there are problems that remain unsolved and require additional studies. In particular, the issue of choosing a scheme of the heat supply system, choosing heat pump units and energy analysis of heat exchange processes is relevant for the practical implementation of geothermal heat supply systems for buildings and structures. The models and methods proposed in most works for evaluating the energy efficiency of ground-source heat pump installations for designers and implementers of heat supply systems for residential buildings are quite complex and highly specialized. Therefore, it is necessary to have a fairly simple and convenient in practical use mathematical model for evaluating the energy efficiency of the pump for the selected scheme of geothermal heat supply. This article offers an exergetic calculation of the coefficient of the degree of thermodynamic perfection for the selection of the appropriate heat pump for the selected scheme of the heat pump installation and real operating conditions.